Will new drugs change the standard of care for patients with mantle cell lymphoma?. Issue 2 (1st February 2016) - Colbourn, Donald S.; Amengual, Jennifer E.; Deng, Changchun; Sawas, Ahmed; O'Connor, Owen A.
ABSTRACT: Mantle Cell lymphoma is a heterogeneous malignancy that has different subtypes with variable levels of aggressiveness. Research on the pathobiology of this disease is helping us understand the etiology for this heterogeneity and has the potential to guide future therapeutic options. The availability of the Ki67 proliferation index and the use of the MIPI score can help determine which of the numerous therapeutic options might be utilized. Minimal Residual Disease testing can act as a guide as to the potential benefit of maintenance therapy. This article discusses the current standard of care for Mantle Cell lymphoma and our current understanding of the pathobiology of the disease leading to strategies to improve patient outcomes with some of the newer targeted agents.